Alcohol abuse in subjects developing or not developing posttraumatic stress disorder after trauma exposure - Marcella Brunetti; Giovanni Martinotti; Gianna Sepede; Federica Vellante; Federica Fiori; Fabiola Sarchione; Massimo di Giannantonio (Archives of Trauma Research, 2017)
Background and Objectives: The complex relation between trauma and alcohol abuse is still far to be recognized. Traumatic experiences can prompt and facilitate an excessive use of alcohol. On the other hand, alcohol use may increase the possibility to be involved in traumatic events or reduce post-trauma resilience. This study aimed to explore alcohol use and abuse in a sample of traumatized participants, with or without posttraumatic stress disorder (PTSD). Methods: Thirty-five outpatients with a Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) diagnosis of PTSD and 35 outpatients with trauma exposure who did not develop PTSD were recruited. The clinical assessment of the participants comprised the following scales: The Structured Clinical Interview for DSM-IV, the Clinician-Administered PTSD Scale, and the Alcohol Use Disorders Identification Test (AUDIT). Results: Correlation analysis conducted on all participants showed a significant positive correlation between the AUDIT score and trauma load. When considering the two groups separately, the same correlation reached statistical significance in the PTSD group only. Analysis of beta-coefficients of regressions confirmed a significant influence of trauma load on the AUDIT score. Conclusion: A greater use of alcohol significantly correlated with trauma load only in the PTSD group. This data indicates that trauma itself is not sufficient to determine drinking problems, whereas PTSD symptoms may lead to alcohol use. A circular relation, rather than a linear one, can therefore be considered when traumatic experiences and alcohol use are taken into account. Specifically, traumatic experiences could cause the PTSD development, which could, in turn, lead to alcohol use or abuse as a self-medication. Such outcome could develop in alcohol use disorder that, circularly, enhances the risk of traumatic experiences. Hence, in the clinical evaluation of PTSD patients, a deep investigation of drinking patterns is highly recommended.